Research on Blockchain-Based FinTech Trust Evaluation Mechanism - Ying Song; Chaohao Sun; Lanxin Li; Feifei Wei; Yueheng Liu; Baolin Sun (IEEE Access, 2023)
The financial technology (FinTech) has promoted the wide application of FinTech with the help of artificial intelligence, blockchain, cloud computing, data science and other new technologies. Trust evaluation has become a forward-looking issue for the rapid development of FinTech. The existing trust evaluation methods of FinTech do not consider the impact of the timeliness, reliability and non-invasive factors of trust on trust evaluation, which results in low accuracy of trust evaluation and incapability of effectively identifying malicious behaviors of users. Firstly, this paper introduces the blockchain technology to construct a four-layer architecture structure and multiple trust evaluation indicators based on blockchain service data. Secondly, the paper proposes a blockchain based FinTech trust evaluation mechanism (BFTEM), which utilizes blockchain to record relevant data and multiple trust parameters during the transmission process of each block, and verify the trust degree issued by the trust holder through the comprehensive trust value of the user. Finally, the block generation time, throughput, delayed response time and comprehensive trust value are experimentally studied through simulation experiments. Simulation experiments show that BFTEM mechanism can better improve the security and reliability of FinTech data, and has advantages in improving the accuracy of trust evaluation and expanding potential applications.